Happiness : Now and Forever - "Singh, Just Win" (New Delhi, 2017)
How to be happy now and forever today, most of us are unhappy because we have become so involved in what we are doing, we have forgotten who is doing. We have literally become human doings instead of remaining of human beings. It is, therefore, essential that before we become emotionally extinct and total machines, we must save ourselves from getting lost into a Mechanical existrance, since we are actually designed for delight. As children we are happy. Then we learned unhappiness. In order to get back to our joy, it is necessary to undo our conditioning and unlearn certain habits which are hindering us from our natural state of happiness. Happiness - now and forever helps you to do just that. It empowers you to remove various self-created obstacles that you may have unintentionally put in your path. It offers simple tips to enable you to align back to happy life now and in every breath of your existence. The action plans suggested in this book will develop you into a happier being who is the master of his emotions no matter what the external circumstances may be. It is time to find out what is stopping you from becoming happy... Now and forever.
Keywords: Self-culture